Doubt: a discovery doctrine in design - Santos, Romilson Marco (Universidade de São Paulo. Faculdade de Arquitetura e Urbanismo., 2017)
This study focuses on understanding the doubt as an inherent factor in the discovery process in design. Therefore, it is necessary to move from creation to discovery in design. It is, in fact, to understand that the doctrine of doubt as a discovery in design is therefore part of the representation of reality from the iconic and indicial signs, to the same extent as we have the suppression of the representation of reality by the symbolic sign. This way, the discovery doctrine in design aims to achieving a less wrong positioning regarding to the design thinking.